Powering a sustainable future: Does economic structure influence the ecological footprint? - Sahoo M.; Kaushik S.; Gupta M.; Islam M.K.; Nayak P. (John Wiley and Sons Ltd, 2025)
To achieve sustainable development goal (SDG) 7 the world needs a lot of catching up. India has been at the forefront of renewable and clean energy missions and its ecological footprint of 0.8 global hectares fares quite well vis--vis the world average. This study, spanning from 1990 to 2021, investigates the impact of structural changes, technological innovation, and renewable energy adoption on India's ecological footprint, utilizing a novel dynamic Autoregressive Distributed Lag (ARDL) simulation for both short and long-term analysis. We find that agriculture exerts a significant increase in the ecological footprint, both in the long run and the short run. Similarly, industry value added has a positive and statistically related to the ecological footprint. However, the result of the service sector indicates negative influence on ecological footprint in the long run, but a positive and significant relation with ecological footprint in the short run. Technological innovation has shown a favorable effect on the environment by reducing ecological footprint. Renewable energy consumption has also enhanced environmental quality by reducing ecological footprint in both short run and long run. To reach SDG 7 goals and lower India's ecological footprint, policy implications include promoting renewable energy, sustainable practices in agriculture and industry, and encouraging technological innovation. ? 2024 ERP Environment and John Wiley & Sons Ltd.